2000
DOI: 10.1038/35020577
|View full text |Cite
|
Sign up to set email alerts
|

NO is necessary and sufficient for egg activation at fertilization

Abstract: The early steps that lead to the rise in calcium and egg activation at fertilization are unknown but of great interest--particularly with the advent of in vitro fertilization techniques for treating male infertility and whole-animal cloning by nuclear transfer. This calcium rise is required for egg activation and the subsequent events of development in eggs of all species. Injection of intact sperm or sperm extracts can activate eggs, suggesting that sperm-derived factors may be involved. Here we show that nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
114
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(117 citation statements)
references
References 24 publications
0
114
3
Order By: Relevance
“…NO is a highly diffusible molecule that plays an important role in mammalian reproductive function, including folliculogenesis [14], fertilization [21], and implantation [7]. Endogenous NO is produced following the conversion of oxygen and L-arginine to NO and L-citrulline, catalyzed by three isoforms of NOS: neuronal NOS (nNOS), endothelial NOS (eNOS), and inducible NOS (iNOS) [12].…”
Section: Introductionmentioning
confidence: 99%
“…NO is a highly diffusible molecule that plays an important role in mammalian reproductive function, including folliculogenesis [14], fertilization [21], and implantation [7]. Endogenous NO is produced following the conversion of oxygen and L-arginine to NO and L-citrulline, catalyzed by three isoforms of NOS: neuronal NOS (nNOS), endothelial NOS (eNOS), and inducible NOS (iNOS) [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the physiological significance of RyR-mediated [Ca 2+ ] i oscilla-tions is questionable, since they do not lead to full egg activation (Ayabe et al, 1995;Fissore et al, 1995;Wu et al, 1997), and because inhibition of this receptor does not perturb fertilization-induced egg activation (Ayabe et al, 1995). The suggestion was also made, based on results from studies in sea urchin eggs, that synthesis of nitric oxide (NO) may act as the initiator of [Ca 2+ ] i release (Kuo et al, 2000). However, studies in ascidian and mouse eggs revealed that fertilizationassociated [Ca 2+ ] i oscillations occur independently of changes in NO concentrations (Hyslop et al, 2001).…”
Section: Fertilization and Inositol 145-trisphosphate (Ip 3 ) Produmentioning
confidence: 99%
“…3 For instance, nNOS plays a fundamental role in the regulation of male sexual function. Lines of evidence have indicated the involvement of nNOS in penile erection, 4 in testosterone synthesis in the Leydig cells of the testis, 5,6 in sexual behavior, [7][8][9] and in egg activation at fertilization, 10 among others. Understanding the molecular regulation of nNOS in male sexual organs may be relevant to potential therapeutic measures in male sexual dysfunction.…”
mentioning
confidence: 99%